Female empowerment and education: a bibliometric analysis - Santos-Rojo, Cristina (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The aim of this study is to produce a rigorous and up-to-date synthesis of education and gender equality in academia. To this end, a bibliometric analysis is carried out in order to evaluate in an objective and quantifiable way the state of the literature on these two aspects. The period under study covers 11 years, starting on 1 January 2011 and ending on 31 December 2021. Thus, the analysis includes a five-year period, before and after 2016, which is considered the official start of the 2030 Agenda. Preliminary results show that research on education and gender equality has moved from North America to Asia. The importance of the topic is confirmed by the high number of studies funded by public and private entities.